Evaluation of steam supply performance: Steamer vs. bubbler - Zhang, Yongliang; Xu, Nansheng; Tang, Qiming; Gibbons, William; Huang, Kevin (Frontiers in Energy Research, 2022)
Water/steam electrolysis is a key enabling technology for clean, low-carbon and sustainable production of hydrogen and will play a crucial role in future hydrogen economy. For high temperature solid oxide electrolytic cells, steam is the chemical feedstock. A stable and accurate supply of steam to solid oxide electrolytic cells is of vital importance to smooth production of hydrogen. In this study, we compare steam supply performance of two commonly used steam generators: steamer and bubbler. Our results show that bubbler with proper volume and fritted inlet gas tubing can provide more stable and accurate steam supply than steamer for laboratory use. We also provide the explanation for the unstable steam supply observed in steamer. Overall, we conclude that bubbler is generally a better choice for small-scale laboratory use (e.g., ≤50%H2O, ≤100 sccm carrier gas flow) to produce stable and accurate steam and steamer might be a better choice for higher steam contents and flow rates (e.g., >60% H2O and >200) encountered in large-scale testing and/or aggressive high steam conditions.